STUDY OF PHYSICAL-MECHANICAL PROPERTIES OF POPLAR WOOD USING HOT STEAM - Tursunov Narimon Sultonboevich (Journals Park Publishing, 2022)
In article it is resulted materials after working out and a substantiation of technology of thermomodifying of wood of the local poplar, allowing to receive a material with the improved physicomechanical characteristics and various architecturally - the art decision.
Keywords: Wood, a poplar, heat treatment, physicomechanical the characteristic